FOSTERING LOYALTY: INVESTIGATING THE COFFEE SHOP WITH SATISFACTION AS AN INTERVENING VARIABLE - Viona Virtuna Abdichianto; Tommy Setiawan Ruslim (Graduate Program of Universitas Tarumanagara, 2024)
In this research, the primary aim is to thoroughly investigate the influence of service quality, food quality, and price fairness on customer loyalty, with customer satisfaction serving as a pivotal mediating variable. The research population encompasses JJ coffee shop patrons in Jakarta. A total of 243 respondents were selected as samples, with criteria including a minimum age, residency, and prior experience dining at the coffee shop. The research utilized purposive sampling, a non-probability sampling technique, along with a specific sample selection method, namely judgmental sampling, was employed for respondent data collection through online questionnaire distribution via Google Forms. The meticulously collected data underwent further in-depth analysis using Partial Least Square Structural Equation Modeling (PLS- SEM) with SmartPLS4 software. The findings indicate that service quality, food quality and price fairness collectively have a positive and significant impact on customer satisfaction. Moreover, customer satisfaction has been found to play a crucial mediating role between service quality, food quality, and price fairness and customer loyalty in the coffee shop business in Jakarta. In addition to contributing to academic knowledge, this study offers actionable insights for JJ coffee shop by highlighting the significance of improving service quality, price fairness, customer satisfaction, and ultimately customer loyalty.